Developing online payment service for tourism businesses at VTC Pay - Nguyễn, Thanh Thảo (2020)
The research purposes; To systematize of theories related to online payment, online payment methods and conditions for its developments in Vietnam. To analyzes the establishment and development of VTC Pay in order to evaluate its achievements and limitations. To forecast and define the development trends in Vietnam market and suggest some solutions to more develop this market in the near future. To figure out the solutions of online payment service for tourism businesses in Vietnam in general and in VTC Pay in particular. The research scope. Scope of spatial research: As a thesis of students' dissertation, the research scope of the topic is of micro scale, limited to a certain enterprise. Specifically, the research scope of the thesis is to study the theory, situation and propose solutions to develop online payment service provider model, focusing on developing online payment services of VTC Pay and focusing on tourism businesses at VTC Pay. Scope of research on time: The limit of research on the time of thesis is the surveyed data from 2017 to 2019 of VTC Pay, combined with external secondary data in within the past 5 years.